Surimi of king weakfish (Macrodon ancylodon) wastes: texture gel evaluation with protease inhibitors and transglutaminase - Kuhn, Claudio Rafael (2012)
Submitted by Sabrina Andrade (sabrinabeatriz@ibest.com.br) on 2011-12-20T01:44:31Z No. of bitstreams: 1 Surimi of king weakfish (Macrodon ancylodon) wastes texture gel evaluation with protease inhibitors and transglutaminase.pdf: 124481 bytes, checksum: 5a50f99015c5fe861714240088cb1e65 (MD5)